2010
DOI: 10.1016/j.geoderma.2010.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of biochar amendments on the quality of a typical Midwestern agricultural soil

Abstract: Biochar, a co-product of thermochemical conversion of lignocellulosic materials into advanced biofuels, may be used as a soil amendment to enhance the sustainability of biomass harvesting. We investigated the impact of biochar amendments (0, 5, 10, and 20 g-biochar kg− 1 soil) on the quality of a Clarion soil (Mesic Typic Hapludolls), collected (0-15 cm) in Boone County, Iowa. Repacked soil columns were incubated for 500 days at 25 °C and 80% relative humidity. On week 12, 5 g of dried and ground swine manure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

71
638
8
18

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,176 publications
(735 citation statements)
references
References 29 publications
71
638
8
18
Order By: Relevance
“…Uzoma et al [52] and Ouyang et al [53] reported improvements in K sat after biochar additions to a silt and sandy loam-textured soil, respectively. In contrast, both Laird et al [47] and Major et al [55] reported no significant change in K sat for biochar applied to loam-and clay-textured soils, respectively. On the other hand, Lim et al [56] reported that K sat values declined after additions of 1, 2, and 5 % (w w −1 ) biochar to both a coarse and a fine sand.…”
Section: Biochar Influence On Soil Water Hydraulicsmentioning
confidence: 90%
See 1 more Smart Citation
“…Uzoma et al [52] and Ouyang et al [53] reported improvements in K sat after biochar additions to a silt and sandy loam-textured soil, respectively. In contrast, both Laird et al [47] and Major et al [55] reported no significant change in K sat for biochar applied to loam-and clay-textured soils, respectively. On the other hand, Lim et al [56] reported that K sat values declined after additions of 1, 2, and 5 % (w w −1 ) biochar to both a coarse and a fine sand.…”
Section: Biochar Influence On Soil Water Hydraulicsmentioning
confidence: 90%
“…Almost 100 years later, Tryon [45] was the first to demonstrate that soil texture was a critical factor controlling the impact of biochar on hydraulic properties. More recently, considerable attention has been given to using biochar to modify soil water hydraulics including water holding capacity and available water content [46][47][48][49][50], as well as soil hydraulic conductivity [51][52][53][54]. Laird et al [47] reported that the addition of 1 to 2 % hardwood biochar to a Midwestern USA Mollisol increased gravity drained water retention by 15 % relative to the untreated control but did not affect soil moisture content measured at soil water potentials of 33 or 1500 kPa (field capacity and wilting point, respectively) [41].…”
Section: Biochar Influence On Soil Water Hydraulicsmentioning
confidence: 99%
“…Recycling nutrients harvested with biomass to adjacent crop lands through soil biochar applications [36] may enhance nutrient use efficiency at a landscape scale. Soil biochar applications may further enhance system sustainability by improving soil quality [34], reducing nutrient leaching [35,39], sequestering C [70], and increasing yields especially on marginal and degraded soils [71].…”
Section: Germplasm To Harvestmentioning
confidence: 99%
“…Enhancing CEC and fertilizer-use efficiency (Steiner et al, 2008 ;Chan et al, 2007;Chan and Xu, 2009), and plant-available water content (Laird et al, 2010;Cornelissen et al, 2013;Tammeorg et al, 2014;Agegnehu et al, 2015). Increased available P (Nurhidayati and Mariati, 2014), and soil-water retention, as well as increase soil water-holding capacity (Laird et al, 2010;Novak et al, 2012;Yu et al, 2013;Mila et al, 2013). The optimum application rate for biochar depends on the specific soil type and crop management (Hunt et al, 2010).…”
Section: Introductionmentioning
confidence: 99%